Assessment of thiol/disulphide homoeostasis and ischaemia-modified albumin and their relationship with disease severity in children with chronic urticaria. (2nd July 2020) - Akdag, Songul; Ozmen, Serap; Ercan, Nazli; Bostanci, Ilknur; Neselioglu, Salim
Abstract: Background: The pathogenesis chronic urticaria (CU) hasn't been fully understood. In recent years, it has been shown that thiol-disulphide homoeostasis, as an antioxidant system, plays important roles in both healthy individuals and various diseases. In different ischaemia-reperfusion states, high oxidative stress causes ischaemia-modified albumin (IMA) generation. Aim: To investigate thiol/disulphide balance and IMA level in children with CU and their association with disease severity. Methods: Thirty children with CU and 20 healthy children as controls, aged 1–18 years, were included in this cross-sectional study. In all subjects, total thiol, native thiol, disulphide levels and IMA levels were measured in plasma by spectrophotometry. Disulphide/native thiol, disulphide/total thiol and native thiol/total thiol ratios were calculated. The disease severity was rated by Urticaria Activity Score (UAS). Results: In the children with CU, the levels of native thiol (375.56 ± 56.22 μmol/L) and total thiol (415.69 ± 54.75 μmol/L) were significantly lower than the control group (475.20 ± 71.87 and 511.20 ± 73.73 μmol/L, respectively) ( p = 0.000, p = 0.000). The ratio of native/total thiol * 100 was lower in patients than the control group ( p = 0.002). IMA was significantly higher in the patient group than control group ( p = 0.000). No significant correlation was found between UAS and thiol/disulphide homoeostasis ( p > 0.05). The disulphide levels, disulphide/native thiol and disulphide/total thiol levels were found to be higher in patients with positive family history for autoimmune disorders than those without ( p < 0.05). Conclusion: In children with CU, impaired thiol/disulphide homoeostasis and increased IMA suggest that oxidative stress may play role in the disease pathogenesis.